Optimizing Engagement: Factors Influencing Family Participation in a Positive Parenting Program among Vulnerable Households with Young Children - Hector Cebolla; Juan Carlos Martín; María José Rodrigo (Psychosocial Intervention)

(untitled)
Objective: This paper addresses a critical gap in family research by examining the risk of families with young children receiving the Minimum Living Income (MLI) in rejecting targeted social interventions, also known as non-take-up (NTU). Method: We analyze recruting process data from the first invitation to participate in a social benefit including the “Growing Happily in the Family-2” program developed in Madrid, Spain, to their written consent prior to its implementation. Measurements of subjective factors reported as reasons for NTU and objective factors of sociodemographic characteristics and detailed household patterns of prior engagement with social services to study NTU response were based on official records and project data. Results: Descriptive findings reveal that jobless parents with high economic hardship, poorer physical and mental health, heavy demanding childbearing, and poor family-job conciliation aggravated by adverse life events profile the NTU response. Linear probability models predicting the rejection/acceptance decision showed that lack of previous contact with the social services, younger parental age, male, and nonimmigrant status significantly elevate NTU risk. Notably, although a longer stay in social services increases the probability of NTU, this does not occur among the most vulnerable families that have received more intensive support, challenging the idea of intervention fatigue. Conclusions: These findings have implications for the design of policies and practices to support children and family as subjects of rights, underlining the need for preventive and capacity-building strategies that address specific barriers to program uptake. Overall, the study highlights innovation areas that lie in the interception of social and employment benefits to improve the reach of the intended population and the positive impact of parenting interventions aimed at supporting vulnerable families.